Efektivitas Pembelajaran Ikatan Kimia dalam Meningkatkan Pemahaman Konsep - Dewi Nur Mauliddiah; Andita Pratiwi; Mila Marliana; Afridha Laily Alindra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to analyze students’ understanding of chemical bonding by using various models, strategies, and media in chemistry instruction. The methodology employed is a Systematic Literature Review (SLR), which involves analyzing scientific articles from 2021 to 2025 obtained through the Google Scholar, Publish or Perish, and Covidence platforms. By utilizing the PRISMA guidelines in the selection process, ten relevant articles were identified. The findings of this study indicate that the application of learning models such as Problem Based Learning (PBL), Discovery Learning, and collaborative learning, as well as the use of technological media such as Augmented Reality (AR), E-Modules, weblogs, and ChemDraw have proven effective in enhancing conceptual understanding, learning outcomes, motivation, and student participation in Chemical Bonding material. Additionally, approaches using diverse representations support students in understanding abstract concepts in a more concrete manner. Therefore, Chemical Bonding instruction can be more effective when supported by innovative learning modelsand interactive media.